PENAMPILAN SIFAT-SIFAT AGRONOMIS BEBERAPA VARIETAS KRISAN DI KABUPATEN BANDUNG - PUTRA, SUNJAYA; OLYNDRIANA DEWI, SRI (Agrotrop : Journal on Agriculture Science, 2012)
Agronomic Performance of Chrysanthemum Varieties in Bandung. The objective of this experiment was to determine the agronomic performance of chrysanthemum varieties in Bandung Regency. The experiment was conducted at District Pasir Jambu Bandung regency of West Java Province on July until October 2010. The materials used are 10 varieties of chrysanthemum: Puspita Nusantara, Padma Buana, Puspita Asri, Purbasari, Swarna Kencana, Cut Nyak Dien, Sakuntala, Tirta Ayuni, Candra Kirana, and Mustika Kaniya. Fertilizers used were fermented manure 30 t / ha, urea 200 kg / ha, SP36 300 kg / ha, and KCl 250 kg / ha, foliar fertilizer Gramoxone 1 cc / l, and pesticides. Randomized block design with ten treatment ofchrysanthemum and four replications. The results of experience conclused that Swarna Kencana, Sakuntala and Padma Buana has a plant height 100.5 cm, 97.6 cm, and 94.76 cm higher than the other varieties (grade A) and the shortest are Candra Kirana of 51.95 cm (grade C). The number of stem segments occurred of Tirta Ayuni varieties in 32.5 and varieties Purbasari 26.2 lowest. Mustika Kaniya has the largest trunk diameter (0.74 cm) and smallest diameter occur on Padma Buana (0.45 cm), Purbasari (0.45 cm) and Puspita Asri (0.46 cm). Tirta Ayuni have leaf length (13.74 cm) and petiole length reached (4.05 cm). The diameter of the largest flower is Sakuntala and the smallest is Candra Kirana. The number of flower Candra Kirana was the smallest (7.7 buds) and most of flowers Purbasari namely 27.30 buds.
Keywords: agronomic performance, variety, crysanthemum.